Analysis of Drinking Water Quality and Sanitary Hygiene at Refill Drinking Water Depots in the Minas Jaya Sub-District Area in 2022: Analisis Kualitas Air Minum Dan Hygiene Sanitasi Pada Depot Air Minum Isi Ulang Di Wilayah Kelurahan Minas Jaya Tahun 2022 - Sarah Hafizah; Yessi Harnani; Winda Septiani; Yeyen Gumayesti; Zulmeliza Rasyid (Badnur Medisa Group, 2022)
Refill drinking water is the treatment of raw water with several stages of the process until it becomes drinking water. The raw water that is usually used in the production process for refill drinking water is sourced from ground water. The water treatment process in principle must be able to remove all types of pollutants, both physical, chemical and microbiological. This research is a qualitative analytic study with a descriptive mode approach that aims to obtain information about the analysis of drinking water quality and sanitation hygiene at refill drinking water depots in the Minas Jaya sub-district, Siak district. January – July 2022. Informants from this study were 9 people divided into 1 environmental health worker at the Puskesmas as key informants, 4 owners of refill water depots as main informants, 4 consumers of water depots in the Minas Jaya village area. The research variables consisted of place, equipment, handlers, inspection of water parameters. The selection of research subjects used purposive (non-propability). The validity of qualitative data using triangulation. Data were analyzed qualitatively. The results of the study concluded that the cleanliness of the place did not meet the health requirements, the equipment had met the health requirements, but the depot worshipers at 4 refill drinking water depots did not meet the health requirements. As well as inspection of water parameters at 4 refill drinking water depots located in Minas Jaya Village, Siak Regency, they have met the health requirements according to the RI Ministry of Health Number 43 of 2014. It was concluded that they had met the eligibility requirements for sanitation hygiene, because in the 4 depots studied, only 3 depots met the requirements and scored above 70%. It is recommended to the drinking water depot to improve the cleanliness of the handlers in wearing work clothes, routinely in carrying out health checks